Advantages of Implementing Contract Farming in Iraq - Al-Tulaibawi, Alaa; Madrazo, Pablo de Frutos; Cervantes , Pedro Antonio Martín (Journal of Ecohumanism, 2024)
This research aims to explore the advantages of implementing contract farming in Iraq and analyze its potential impacts on the agricultural sector. The study focuses on how contract farming can improve farmers' incomes, stabilize prices, and increase agricultural productivity. Contract farming can enhance farmers' access to markets and modern agricultural technologies. The study examines economic and social benefits, alongside the challenges of implementation, particularly given Iraq's fragile agricultural infrastructure. Based on a review of the current literature, the study finds that contract farming presents a crucial option for developing Iraq's agricultural sector by providing sustainable support to farmers and reducing marketing and production risks. The research emphasizes the need for a partnership between the public and private sectors to ensure the success of this strategy, with policy recommendations aimed at improving the efficiency of the agricultural system and supporting local farmers.